Evolution of the spectrum of the Hubbard model with filling - Sherman, A. (Condensed Matter Physics, 2006)
The diagram technique for the one-band Hubbard model is formulated for the case of moderate to strong
Hubbard repulsion. The expansion in powers of the hopping constant is expressed in terms of site cumulants
of electron creation and annihilation operators. For Green’s function an equation of the Larkin type is derived
and solved in a one-loop approximation for the case of two dimensions and nearest-neighbor hopping. With
decreasing the electron concentration in addition to the four bands observed at half-filling, a narrow band
arises near the Fermi level. The dispersion of the new band, its bandwidth and the variation with filling are
close to those of the spin-polaron band in the t-J model. Сформульовано дiаграмну технiку для однозонної моделi Хаббарда для випадку промiжного та сильного хаббардiвського вiдштовхування. Розклад за степенями константи перескоку виражено через
вузловi кумулянти електронних операторiв народження та знищення. Отримано рiвняння Ларкiна
для функцiї Грiна та розв’язано його у однопетлевому наближеннi для двовимiрного випадку та переносу мiж найближчими сусiдами. При пониженнi електронної концентрацiї крiм чотирьох зон, що
iснують при половинному заповненнi, з’являється вузька зона поблизу рiвня Фермi. Дисперсiя цiєї
нової зони, її ширина та змiна при змiнi концентрацiї є подiбними до таких же величин для випадку
спiн-поляронної зони в t-J моделi.